2012
DOI: 10.1002/ca.22118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cartilage and menisci on the sagittal slope of the tibial plateaus

Abstract: We analyzed the magnetic resonance studies of the knee in 80 subjects, 45 men and 35 women with a mean age of 38.9 years, who showed no pathological condition of the joint. Using an imaging visualization software, the sagittal longitudinal axis of the tibia was identified. The angle between this axis and a line tangent to the bone profile of the tibial plateau (bone slope) and to the superior border of the menisci (meniscal slope) were calculated. Thickness of anterior and posterior portion of menisci and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Therefore, the ellipse as a simplified representation of two circles could also be accepted as representing the sagittal shape of the lateral femoral condyle. The lack of correlation could be explained by the fact that the lateral compartment always exhibits relative laxity to the medial side (Tokuhara, Kadoya, Nakagawa, Kobayashi, & Takaoka, ), because of the lower tension of the lateral collateral ligament and greater movement of the lateral meniscus (Cinotti et al, ). Therefore, in our study, the lPTS showed a broader range of values than the mPTS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ellipse as a simplified representation of two circles could also be accepted as representing the sagittal shape of the lateral femoral condyle. The lack of correlation could be explained by the fact that the lateral compartment always exhibits relative laxity to the medial side (Tokuhara, Kadoya, Nakagawa, Kobayashi, & Takaoka, ), because of the lower tension of the lateral collateral ligament and greater movement of the lateral meniscus (Cinotti et al, ). Therefore, in our study, the lPTS showed a broader range of values than the mPTS.…”
Section: Discussionmentioning
confidence: 99%
“…The meniscus has various biomechanical functions, including shock absorption, load transmission, and passive stabilization. 9,12 Shock absorption and load transmission are generally accepted as 2 of its most important functions. The meniscus distributes compressive force across the tibiofemoral joint by converting it to tensile stress along its circumferential collagen fibers.…”
mentioning
confidence: 99%
“…Sagittal orientations were assessed as a line tangent to the greatest part of the superior bone profile, and on the lateral side, the orientations were assessed as a line tangent to most of the superior bone profile. 9 As described earlier by Cinotti et al, when the sagittal slope between the medial and lateral plateaus differed, the two values were averaged. 9 A parallel line was drawn to the sagittal inclination line at 3 mm below the most defective part of cartilage of the medial tibia plateau for a minimal tibial cut.…”
Section: Calculationmentioning
confidence: 99%
“…8 Because wide variations occur in the general population in the PTS, tibial cuts that are parallel to normal PTS could result in smaller flexion gaps in patients with lower tibial slopes, or injury to the PCL insertion in patients with higher tibial slopes. 9 Recent investigations have also shown that a standard tibial cut performed parallel to the PTS might result in the detachment of most PCL fibers from their insertion in the proximal tibia. 10,11 When the PTS was more than 8 degrees and the tibial cut was performed at 0 degree, a preservation of PCL insertion more than 50% was found in only 31% of cases.…”
mentioning
confidence: 99%